2007
DOI: 10.1093/jhmas/jrm002
|View full text |Cite
|
Sign up to set email alerts
|

The Military, Psychiatry, and "Unfit" Soldiers, 1939 1942

Abstract: This article examines the psychiatric screening of U.S. soldiers during the Second World War, established by psychiatrist Harry Stack Sullivan (1892-1949), as a key moment in the public application of clinical psychiatry, as well as a turning point in Sullivan's intellectual and professional career. After a brief look at the ideas and expectations Sullivan brought to the screening system, I discuss a major problem of the screening: the mismatch between the medical concept of disease prevention and the realitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…When he became a high‐level consultant to the U.S. Selective Service in 1940, one of his most critical tasks was to train physicians to assess selectees (Sullivan, 1941; Wake, 2007). The goal was to weed out “maladjusted” men before they ever put on a uniform.…”
Section: A Neo‐freudian's Warmentioning
confidence: 99%
“…When he became a high‐level consultant to the U.S. Selective Service in 1940, one of his most critical tasks was to train physicians to assess selectees (Sullivan, 1941; Wake, 2007). The goal was to weed out “maladjusted” men before they ever put on a uniform.…”
Section: A Neo‐freudian's Warmentioning
confidence: 99%
“…There were two primary reasons for this: the first was that 12 per cent of all men who volunteered for military duty were rejected on psychiatric grounds, amounting to more than a million people, six times the rejection figure for the First World War (Pols and Oak, 2007). Although historian Naoko Wake has highlighted how a considerable percentage of this figure amounted to homosexuals (which was considered a mental illness), it nonetheless suggested that far more Americans were mentally ill than previously thought (Wake, 2007). The second reason, as Jackson (2013) and others have described, was increased recognition of combat stress, highlighted in Grinker and Spiegel's study Men Under Stress (1945).…”
Section: Introductionmentioning
confidence: 99%
“…76 Men in this period who did not display suitably masculine aggressiveness were routinely accused of homosexuality 77 and were seen to pose 'unquestionable harm to "normal" soldiers.' 78 Lancelot becomes a 'surrogate character' for these desires and frustrations.…”
mentioning
confidence: 99%